Cannabinoid WIN55,212-2 reprograms monocytes and macrophages to inhibit LPS-induced inflammation - Pérez-Diego, Mario; Angelina, Alba; Martín-Cruz, Leticia; de la Rocha-Muñoz, Andrés; Maldonado, Angel; Sevilla-Ortega, Carmen; Palomares, Oscar (Frontiers in Immunology, 2023)
Introduction Chronic or uncontrolled activation of myeloid cells including monocytes, macrophages and dendritic cells (DCs) is a hallmark of immune-mediated inflammatory disorders. There is an urgent need for the development of novel drugs with the capacity to impair innate immune cell overactivation under inflammatory conditions. Compelling evidence pointed out cannabinoids as potential therapeutic tools with anti-inflammatory and immunomodulatory capacity. WIN55,212-2, a non-selective synthetic cannabinoid agonist, displays protective effects in several inflammatory conditions by mechanisms partially depending on the generation of tolerogenic DCs able to induce functional regulatory T cells (Tregs). However, its immunomodulatory capacity on other myeloid cells such as monocytes and macrophages remains incompletely understood. Methods Human monocyte-derived DCs (hmoDCs) were differentiated in the absence (conventional hmoDCs) or presence of WIN55,212-2 (WIN-hmoDCs). Cells were stimulated with LPS, cocultured with naive T lymphocytes and their cytokine production and ability to induce T cell responses were analysed by ELISA or flow cytometry. To evaluate the effect of WIN55,212-2 in macrophage polarization, human and murine macrophages were activated with LPS or LPS/IFNγ, in the presence or absence of the cannabinoid. Cytokine, costimulatory molecules and inflammasome markers were assayed. Metabolic and chromatin immunoprecipitation assays were also performed. Finally, the protective capacity of WIN55,212-2 was studied in vivo in BALB/c mice after intraperitoneal injection with LPS. Results We show for the first time that the differentiation of hmoDCs in the presence of WIN55,212-2 generates tolerogenic WIN-hmoDCs that are less responsive to LPS stimulation and able to prime Tregs. WIN55,212-2 also impairs the pro-inflammatory polarization of human macrophages by inhibiting cytokine production, inflammasome activation and rescuing macrophages from pyroptotic cell death. Mechanistically, WIN55,212-2 induced a metabolic and epigenetic shift in macrophages by decreasing LPS-induced mTORC1 signaling, commitment to glycolysis and active histone marks in pro-inflammatory cytokine promoters. We confirmed these data in ex vivo LPS-stimulated peritoneal macrophages (PMΦs), which were also supported by the in vivo anti-inflammatory capacity of WIN55,212-2 in a LPS-induced sepsis mouse model. Conclusion Overall, we shed light into the molecular mechanisms by which cannabinoids exert anti-inflammatory properties in myeloid cells, which might well contribute to the future rational design of novel therapeutic strategies for inflammatory disorders.